2016
DOI: 10.1080/12507970.2016.1216340
|View full text |Cite
|
Sign up to set email alerts
|

Cross canal, Drive et relation de services : une analyse par la boucle de service

Abstract: International audienceThis article aims to study drive-in users’ experience (from a numerical and physical point of view). It focuses on overall drive-in users’ satisfaction by carrying out an empirical study in Brittany. In terms of the results, a flowchart of the drive-in store’s added value will be presented from a customer experience perspective. The drive-in store’s weak points caused by the new service offering will also be examined.L’objectif de cet article est d’étudier le parcours du client en Drive, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
0
1
Order By: Relevance
“…Our results add furthermore that the positive effects of the interaction terms between convenience and both the PQFP and the perceived quality of logistics service on satisfaction can lead to higher purchase incidence in drive-throughs. These results are in contrast with that of Mevel et al (2016), who showed, for example, that the quality of service was one of the weaknesses of the drive-through industry. Consequently, our research points out the complexity for retailers in transforming their business models are based on offline channels (mainly hypermarkets) by offering new formats, which bring contributions to society.…”
Section: Discussioncontrasting
confidence: 93%
“…Our results add furthermore that the positive effects of the interaction terms between convenience and both the PQFP and the perceived quality of logistics service on satisfaction can lead to higher purchase incidence in drive-throughs. These results are in contrast with that of Mevel et al (2016), who showed, for example, that the quality of service was one of the weaknesses of the drive-through industry. Consequently, our research points out the complexity for retailers in transforming their business models are based on offline channels (mainly hypermarkets) by offering new formats, which bring contributions to society.…”
Section: Discussioncontrasting
confidence: 93%